Resveratrol and quercetin-induced apoptosis of human 232B4 chronic lymphocytic leukemia cells by activation of caspase-3 and cell cycle arrest. (1st May 2013) - Gokbulut, Aysun Adan; Apohan, Elif; Baran, Yusuf
Abstract : Chronic lymphocytic leukemia (CLL), defined by accumulation of pathogenic B cells, has a very complex biology due to various factors such as inherited, host, and enviromental factors. Recently, finding new therapeutic agents or development of novel treatment strategies have been paid attention. Resveratrol and quercetin, important phytoalexins found in many plants, have been reported to have cytotoxic effects on various types of cancer. In this study, we examined cytotoxic, cytostatic, and apoptotic effects of these two important phenolic compounds on 232B4 human CLL cells. Cytotoxic effects of resveratrol and quercetin were determined by MTT cell proliferation assay. Changes in caspase-3 enzyme activity were measured using caspase-3 colorimetric assay. Annexin V-FITC/PI double staining was performed to measure apoptotic cell population. Effects of resveratrol and quercetin on cell cycle profiles of CLL cells were investigated by flow cytometry. Treatment of CLL cells with resveratrol and quercetin caused dose dependent inhibition of cell proliferation and increased apoptotic cell population through induction of caspase-3 activity. Cell cycle analysis displayed cell cycle arrest mainly in G0/G1 for both polyphenols. Our data, in total, showed for the first time that resveratrol and quercetin might block CLL growth through inducing apoptosis and cell cycle arrest.